THE SCIENCE OF STORY-TELLING. - Perez, Tony (Tin House)
An interview with Jad Abumrad and Robert Krulwich, hosts in the radio program "Radiolab," is presented. When asked about a certain factor which triggers the collaboration of the show's writers, Abumrad refers to their attitude, while Krulwich described them as educators. They discuss the concept of the program, particularly in science journalism. They explain the balance of the emotional and hard science aspects in the show.